PENINGKATAN PENGELOLAAN KEUANGAN BERBASIS EXCEL PADA BADAN USAHA MILIK DESA - Animah; Widia Astuti; Robith (Buletin SWIMP, 2021)
Giri Sasak Village is one of the new expansion villages where the majority of the people are farmers, therefore the community's spending pattern is at harvest time they will spend more on basic needs, while daily needs are almost said to be no expenditure. However, when there are non-routine expenses, such as marriage, death, and circumcision, they tend to owe money to moneylenders. However, this does not have a better impact on society. Thus, the existence of BUMDes is very helpful in meeting the needs of the community. Based on observations, BUMDes managers do not understand properly how to manage finances properly. To improve the financial management of the Giri Sasak Village BUMDes, the service team conducted training and mentoring for the Giri Sasak Village BUMDes regarding how to manage finances with an excel-based information system.